Assessing impacts of pathogen-tested sweetpotato planting materials in Central Luzon, Philippines - Basilio, Carlos; Tablarin, Rizalina; Porciuncula, Fe; Dolores, Lolit (2005)
Sweet potato production in Central Luzon, Philippines has been plagued by a virus disease complex locally known as “camote kulot.” Aside from causing more than 50% reduction in yield, the disease was also responsible for the loss of an important variety with good and well-accepted agronomic characteristics. Interagency efforts resulted in a technology in the production of clean planting materials through thermotheraphy and meristem culture. A sweetpotato variety has been cleaned up, reproduced and multiplied for farmers use. CIP-UPWARD supported the use of participatory R&D approaches to adapt CPM in sweetpotato-associated livelihood systems in the region. The program implemented livelihood systems analysis, farmer field schools and farmer participatory researches. Several technical and socio-economic evaluation activities were also conducted to determine the contribution of these projects and CPM in livelihood systems. The results indicated the role of participatory approaches in facilitating project outputs and outcomes. PR&D approaches intensify awareness of research and development institutions about “kulot” and the potential of CPM in solving it leading to their provision of resources and other support to its solution. CPM were produced and used by 117 farmers in 19 villages of the provinces of Tarlac and Bataan. Local government units provided their own resources to so that their constituents will benefit from the technology. They build nethouses, finance FFS and mobilize communities leading to establishment of enterprises out of CPM technology. Unfortunately, there are a number of technical, socio-economic and policy issues that limits more widespread use of CPM and improvements in contributions of sweetpotato to the livelihood systems of households in the region. The paper also looks at the various elements of participatory research and development, how they have been operationalized within the project context and how they have contributed to achieving project outcomes and impacts. These elements evolved from UPWARD’s own field-based experiences and from efforts by other organizations to develop a wide range of participatory approaches. The paper explores the use of the following elements - problem-based agenda, impact-driven objectives, field-based action, user responsiveness, household orientation, livelihood systems framework, integration of scientific and local knowledge, interdisciplinary mode and inter-institutional partnerships, as touchstones for assessing PR&D processes.